Logikós: Augmenting the Web with Multi-criteria Decision Support - Fernández, Alejandro (2019)
There are activities that on-line customers daily perform, which involve a multi-criteria decision challenge. Choosing a destination for traveling, buying a book to read, or buying a mobile phone are some examples. Customers analyze and compare alternatives considering a set of shared characteristics, and under certain criteria. E-commerce web-sites frequently present the information of products without special support to compare them by one or many properties. Moreover support for decision making is limited to sorting, filtering, and side-by-side comparison tables. Consequently, customers may have the feeling that the merchants interests influence their choices, which are no longer grounded on the rational arguments they would like to put in practice. Moreover, the alternatives of interest for the customer are frequently scattered across various shops, with no support to collect and compare them in a consistent and customized manner. In this article, we propose empowering users with multi-criteria decision making support on any website, and across different websites. We also present Logik ́os, a toolbox supporting multi-criteria decision making depending on the presentation layer of any Web page.